2016
DOI: 10.1080/09064710.2016.1178324
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of ammonium toxicity by silicon in tomato depends on the ammonium concentration

Abstract: Ammonium toxicity in hydroponically grown crops can affect tomato development. However, it has been shown that the silicon (Si) attenuates ammonium toxicity in plants depending on the plant species, the stage of development and the ammonium concentration in the nutrient solution. Thus, in order to investigate how Si attenuates stress caused by ammonium in tomato, a study was carried out involving plants cultivated up to 40 days after seed germination using nutrient solutions containing ammonium concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
(20 reference statements)
2
24
0
Order By: Relevance
“…However, few studies have investigated how the effects of N forms can affect the development and partition of root biomass. The high NH 4 + ratios decrease the total N accumulation in the dry matter of species considered as sensitive to excess ammonium, such as Brassica napus L. (Madsen & Pan, ; Pan et al., ) Cucumis sativus (Campos et al., ; Roosta et al., ), Vicia faba L. (Pan et al., ) Triticum aestivum ( Horchani et al., ; Pan et al., ), Solanum lycopersicum (Barreto et al., ), and Oryza sativa and Spinacia oleracea (Silva, Mello Prado, & Ferreira, ), as well as in tolerant species, such as Saccharum spp . (Ishikawa et al., ) and Passiflora edulis (Silva Júnior et al., ).…”
Section: Ammonium Toxicity Effects From a Crop‐physiology Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have investigated how the effects of N forms can affect the development and partition of root biomass. The high NH 4 + ratios decrease the total N accumulation in the dry matter of species considered as sensitive to excess ammonium, such as Brassica napus L. (Madsen & Pan, ; Pan et al., ) Cucumis sativus (Campos et al., ; Roosta et al., ), Vicia faba L. (Pan et al., ) Triticum aestivum ( Horchani et al., ; Pan et al., ), Solanum lycopersicum (Barreto et al., ), and Oryza sativa and Spinacia oleracea (Silva, Mello Prado, & Ferreira, ), as well as in tolerant species, such as Saccharum spp . (Ishikawa et al., ) and Passiflora edulis (Silva Júnior et al., ).…”
Section: Ammonium Toxicity Effects From a Crop‐physiology Pointmentioning
confidence: 99%
“…plants cultivated with high ammonium, thus increasing leaf and stem dry matter production. Studies on the interaction between silicon and excess ammonium in Zea mays (Campos et al., ), Cucumis sativus (Campos et al., ), Solanum lycopersicum (Barreto et al., ), and Brassica oleracea (Barreto et al., ) indicated that the use of the beneficial element alleviated the ammonium toxicity, with an increase in the N and Si accumulation and the photosynthetic activities, thus providing higher plant dry matter accumulation.…”
Section: Management Strategies To Allow Best Use Of N‐nh4+ Supplies: mentioning
confidence: 99%
“…After 5 d of emergency, thinning was made leaving four plants in each pot, allowing adequate distance for root growth. Substrate mixture of (1:1, v/v) medium vermiculite (90 to 100% of the particles between 1.19 and 1.50 mm) and superfine (90 to 100% of the particles between 0.21 and 0.30 mm) was used, allowing for adequate porosity and aeration (Sarasketa et al, 2014;Barreto et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in the cultivation of Solanum lycopersicum verified a linear decrease of dry matter with the use of ammonium concentrations higher than 1 mmol L -1 in the nutrient solution (Barreto et al, 2016). In other research on different species, the effect of NH 4 + toxicity can also be verified, and its critical concentration of toxicity in plants such as Lemna minor, with 3.3 mmol L -1 of NH 4 + (Huang et al, 2013), and Solanum tuberosum, with 4.1 mmol L -1 of NH 4 + (Zebarth et al, 2012).…”
mentioning
confidence: 93%
See 1 more Smart Citation